Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Find the first five terms in sequences with the following nth terms:

a. [tex]\(9n - 1\)[/tex]
b. [tex]\(4n - 2\)[/tex]
c. [tex]\(6n + 1\)[/tex]
d. [tex]\(2n^2 - 1\)[/tex]

a. The first five terms of [tex]\(9n - 1\)[/tex] are [tex]\(\square\)[/tex], [tex]\(\square\)[/tex], [tex]\(\square\)[/tex], [tex]\(\square\)[/tex], and [tex]\(\square\)[/tex]. (Simplify your answers. Use ascending order.)


Sagot :

Sure! Let's find the first five terms for each of the given sequences step-by-step:

1. Sequence with nth term given by [tex]\( 9n - 1 \)[/tex]:
- For [tex]\( n = 1 \)[/tex], the term is [tex]\( 9(1) - 1 = 9 - 1 = 8 \)[/tex]
- For [tex]\( n = 2 \)[/tex], the term is [tex]\( 9(2) - 1 = 18 - 1 = 17 \)[/tex]
- For [tex]\( n = 3 \)[/tex], the term is [tex]\( 9(3) - 1 = 27 - 1 = 26 \)[/tex]
- For [tex]\( n = 4 \)[/tex], the term is [tex]\( 9(4) - 1 = 36 - 1 = 35 \)[/tex]
- For [tex]\( n = 5 \)[/tex], the term is [tex]\( 9(5) - 1 = 45 - 1 = 44 \)[/tex]

So, the first five terms of [tex]\( 9n - 1 \)[/tex] are [tex]\( 8 \)[/tex], [tex]\( 17 \)[/tex], [tex]\( 26 \)[/tex], [tex]\( 35 \)[/tex], and [tex]\( 44 \)[/tex].

2. Sequence with nth term given by [tex]\( 4n - 2 \)[/tex]:
- For [tex]\( n = 1 \)[/tex], the term is [tex]\( 4(1) - 2 = 4 - 2 = 2 \)[/tex]
- For [tex]\( n = 2 \)[/tex], the term is [tex]\( 4(2) - 2 = 8 - 2 = 6 \)[/tex]
- For [tex]\( n = 3 \)[/tex], the term is [tex]\( 4(3) - 2 = 12 - 2 = 10 \)[/tex]
- For [tex]\( n = 4 \)[/tex], the term is [tex]\( 4(4) - 2 = 16 - 2 = 14 \)[/tex]
- For [tex]\( n = 5 \)[/tex], the term is [tex]\( 4(5) - 2 = 20 - 2 = 18 \)[/tex]

So, the first five terms of [tex]\( 4n - 2 \)[/tex] are [tex]\( 2 \)[/tex], [tex]\( 6 \)[/tex], [tex]\( 10 \)[/tex], [tex]\( 14 \)[/tex], and [tex]\( 18 \)[/tex].

3. Sequence with nth term given by [tex]\( 6n + 1 \)[/tex]:
- For [tex]\( n = 1 \)[/tex], the term is [tex]\( 6(1) + 1 = 6 + 1 = 7 \)[/tex]
- For [tex]\( n = 2 \)[/tex], the term is [tex]\( 6(2) + 1 = 12 + 1 = 13 \)[/tex]
- For [tex]\( n = 3 \)[/tex], the term is [tex]\( 6(3) + 1 = 18 + 1 = 19 \)[/tex]
- For [tex]\( n = 4 \)[/tex], the term is [tex]\( 6(4) + 1 = 24 + 1 = 25 \)[/tex]
- For [tex]\( n = 5 \)[/tex], the term is [tex]\( 6(5) + 1 = 30 + 1 = 31 \)[/tex]

So, the first five terms of [tex]\( 6n + 1 \)[/tex] are [tex]\( 7 \)[/tex], [tex]\( 13 \)[/tex], [tex]\( 19 \)[/tex], [tex]\( 25 \)[/tex], and [tex]\( 31 \)[/tex].

4. Sequence with nth term given by [tex]\( 2n^2 - 1 \)[/tex]:
- For [tex]\( n = 1 \)[/tex], the term is [tex]\( 2(1^2) - 1 = 2(1) - 1 = 2 - 1 = 1 \)[/tex]
- For [tex]\( n = 2 \)[/tex], the term is [tex]\( 2(2^2) - 1 = 2(4) - 1 = 8 - 1 = 7 \)[/tex]
- For [tex]\( n = 3 \)[/tex], the term is [tex]\( 2(3^2) - 1 = 2(9) - 1 = 18 - 1 = 17 \)[/tex]
- For [tex]\( n = 4 \)[/tex], the term is [tex]\( 2(4^2) - 1 = 2(16) - 1 = 32 - 1 = 31 \)[/tex]
- For [tex]\( n = 5 \)[/tex], the term is [tex]\( 2(5^2) - 1 = 2(25) - 1 = 50 - 1 = 49 \)[/tex]

So, the first five terms of [tex]\( 2n^2 - 1 \)[/tex] are [tex]\( 1 \)[/tex], [tex]\( 7 \)[/tex], [tex]\( 17 \)[/tex], [tex]\( 31 \)[/tex], and [tex]\( 49 \)[/tex].

Therefore, the first five terms for the sequences are:

a. The first five terms of [tex]\( 9n - 1 \)[/tex] are [tex]\( 8, 17, 26, 35, \)[/tex] and [tex]\( 44 \)[/tex].